2015
DOI: 10.4085/1062-6050-50.5.07
|View full text |Cite
|
Sign up to set email alerts
|

Weight-Bearing Dorsiflexion Range of Motion and Landing Biomechanics in Individuals With Chronic Ankle Instability

Abstract: Context: People with chronic ankle instability (CAI) exhibit less weight-bearing dorsiflexion range of motion (ROM) and less knee flexion during landing than people with stable ankles. Examining the relationship between dorsiflexion ROM and landing biomechanics may identify a modifiable factor associated with altered kinematics and kinetics during landing tasks.Objective: To examine the relationship between weightbearing dorsiflexion ROM and single-legged landing biomechanics in persons with CAI.Design: Cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 37 publications
(63 reference statements)
6
61
1
1
Order By: Relevance
“…A prospective study revealed that limited dorsiflexion range of motion (ROM) has been identified as a strong risk factor for LAS . It is believed that static arthrokinematic restriction could limit dorsiflexion during functional tasks, resulting in a decreased ability to absorb GRF effectively via eccentrically controlled plantarflexors . We believe that observed increases in vertical and posterior GRF could be due to decreased dorsiflexion angle during mid‐landing (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study revealed that limited dorsiflexion range of motion (ROM) has been identified as a strong risk factor for LAS . It is believed that static arthrokinematic restriction could limit dorsiflexion during functional tasks, resulting in a decreased ability to absorb GRF effectively via eccentrically controlled plantarflexors . We believe that observed increases in vertical and posterior GRF could be due to decreased dorsiflexion angle during mid‐landing (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Correlations were interpreted as weak (0.00–0.40), moderate (0.41–0.69), or strong (0.70–1.00) (Hoch et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Specifically, researchers have suggested that both mechanical and sensorimotor insufficiencies may be present in those with CAI 5. Identified mechanical insufficiencies include arthrokinematic restrictions,20 21 ligamentous laxity22–24 and joint degeneration,25 whereas sensorimotor deficiencies such as diminished static26–28 and dynamic postural control,29–31 loss of strength32 33 and altered spinal reflex excitability34–36 have also been found in patients with CAI. This has led to the development of several therapeutic interventions such as balance training,37–39 resistive training,40 41 joint mobilisation42 43 and multimodal rehabilitations44 45 programmes that have all led to the improvements in the mechanical and sensorimotor insufficiencies previously mentioned.…”
Section: Introductionmentioning
confidence: 99%